Nonsteroideal Anti-inflammatory Drugs (NSAIDs) in clinical practice: managing gastric and cardiovascular risks - Fanelli, Andrea; Ghisi, Daniela; Fanelli, Guido (Acta Biomedica Atenei Parmensis, 2013)
For many years, non-steroidal inflammatory drugs (NSAIDs) were commonly used in the treatment of acute pain due to inflammation.With the arrival on the market of NSAIDs with selective action on COX-2 there was a reduction of side effects in the stomach, but not eliminating the possible cardiovascular complications. The availability of NSAIDs such self-medication can aggravate this type of problem, it is therefore the clinician a fair and accurate assessment of the risk \ benefit based on the characteristics of the individual patient.